If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 + -8x = -4(-6 + 3x) 40 + -8x = (-6 * -4 + 3x * -4) 40 + -8x = (24 + -12x) Solving 40 + -8x = 24 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 40 + -8x + 12x = 24 + -12x + 12x Combine like terms: -8x + 12x = 4x 40 + 4x = 24 + -12x + 12x Combine like terms: -12x + 12x = 0 40 + 4x = 24 + 0 40 + 4x = 24 Add '-40' to each side of the equation. 40 + -40 + 4x = 24 + -40 Combine like terms: 40 + -40 = 0 0 + 4x = 24 + -40 4x = 24 + -40 Combine like terms: 24 + -40 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 48-8*3= | | (1x^2+7x-2)=0 | | 8s-12=24+5s | | 7(u-1)=4u+8 | | 48-8*2= | | 9(3x-2x)=2(10-8x) | | 7(y+9)=92 | | s-y=w | | 50-6*6= | | -5-6(3b+1)=39-8b | | -5x-6(x-5)=-x+30 | | 4(w+3)=8w | | 3x-11=x^2-9 | | D^2+8*d+9=0 | | 15-3*4= | | 4x^2-5=-5x+3 | | 3x+24y=9 | | -(8-4r)=-5+4r | | 24x^2+2xy-y^2=0 | | 23+5x=-2(x+6) | | 7(1+8v)+2v=7-6v | | 6(1-2x)-5=-83 | | 24x^2+2xr-r^2=0 | | 2x^3+x^2-19x+36=y | | -[2]=x-9 | | -2(v+3)=-18 | | x^2+1.68=2.6x | | 5(-4+m)=-45 | | 2x^3+x^2-19x+36=x | | -5r-3=-33 | | 6(4x+7)=105 | | 5(n+5)=34+8n |